IMPACT OF AN EDUCATIONAL CURRICULUM TO DEVELOP TECHNICAL PERFORMANCE OF SOME BASIC SKILLS IN MINI-VOLLEYBALL - Ahmed Hassan Saber Alkaabi (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Mini-volleyball is a simplified version of volleyball designed to suit young learners and can be played in smaller spaces, both indoors and outdoors. It is widely used as an introductory platform to develop fundamental motor and technical skills among children. However, many young players lack access to structured and age-appropriate training programs. Objectives. The research aims to develop a proposed educational curriculum to develop some basic skills among mini-volleyball players in the experimental group. Identifying impact of proposed educational curriculum to develop basic skills among mini-volleyball players in the experimental group. Method. The researcher adopted an experimental approach involving a pre-test and post-test design with two groups: experimental and control. The sample consisted of 16 participants (aged 9–12 years) randomly selected from a specialized football school in Maysan, drawn from a total population of 30 students. The experimental group followed the newly designed educational curriculum, while the control group received conventional instruction. Results. Analysis of pre- and post-test data indicated significant improvement in both groups, with the experimental group demonstrating superior gains in technical skill performance. The curriculum was effective in systematically enhancing the targeted skills. Conclusion. The proposed educational curriculum positively influenced the technical development of mini-volleyball players, particularly in serving, receiving, and setting. These results support the integration of structured and developmentally appropriate curricula in youth training programs to optimize learning outcomes.